Electrochemical Probe for Frictional Force and Bubble Measurements in Gas-Liquid-Solid Contactors and Innovative Electrochemical Reactors for Electrocoagulation/Electroflotation - Essadki, Abdel Hafid (IntechOpen, 2012)
None